2001
DOI: 10.1515/znc-2001-9-1006
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Investigations of Virola oleifera Leaves

Abstract: A methanolic extract and two fractions (n-hexane and ethyl acetate) from Virola oleifera leaves and some compounds (one lignan and two flavonoids) were investigated to verify the analgesic activity by using the writhing test in mice. The crude methanolic extract showed a moderate analgesic effect (about 40% of inhibition in this test at 10 mg/kg), whereas n-hexane and ethyl acetate fractions caused inhibition of 51.3 ± 5.9% and 50.5 ± 6.3% , respectively. Oleiferin-C (1), a lignan isolated from the n-hexane fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Phenolic acids, sesquiterpene lactones, lignans, tannins and triterpenes found in A. millefolium and A. vulgaris (Heinrich et al, 1998;Lorenzi and Matos, 2002) are classes that present analgesic and/or antiinflammatoryrelated effects (da Silva et al, 2001(da Silva et al, , 2005Kuroshima et al, 2001;Spessoto et al, 2003;Gaertner et al, 1999). Furthermore, some alkaloids exhibit a potent analgesic effect; however, only traces of these constituents were found in the two plants.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids, sesquiterpene lactones, lignans, tannins and triterpenes found in A. millefolium and A. vulgaris (Heinrich et al, 1998;Lorenzi and Matos, 2002) are classes that present analgesic and/or antiinflammatoryrelated effects (da Silva et al, 2001(da Silva et al, , 2005Kuroshima et al, 2001;Spessoto et al, 2003;Gaertner et al, 1999). Furthermore, some alkaloids exhibit a potent analgesic effect; however, only traces of these constituents were found in the two plants.…”
Section: Discussionmentioning
confidence: 99%
“…1), was isolated from the rhizome of Smilax glabra, a Liliaceae plant. The flavanone was also reported in many other plants such as Dimrophandra mollis, Hypericum perforatum, Virola oleifera, and Engelhardtia chrysolepis et al [1][2][3][4]. In some wines such as Chardonnay, Pinot Noir vintages, and French varietal wines, the existence of astilbin was also detected [5,6].…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies reported the presence of resveratrol, quercetin, quercitrin and kaempferol in C. quadrangularis [11,13], and all these phenolic compounds were reported to possess good analgesic effect in previous studies [34][35][36][37][38][39]. Hence, the analgesic effect of CQME may be attributed to the presence of phenolic compounds.…”
Section: Discussionmentioning
confidence: 94%